Effects of edible coatings enriched with calcium chloride on physiological, biochemical and quality responses of mango (Mangifera indica L. cv. Choke anan) fruit during cold storage - Khaliq, Ghulam (2015)
Mango is a climacteric fruit and various biochemical changes during ripening affect the fruit composition. It is very sensitive to chilling temperature during storage. In the first experiment, the effects of gum arabic (GA) 10%, chitosan (CH) 1%, calcium chloride (CA) 3 %, GA 10% + CH 1%, GA 10% + CA 3%, CH 1% + CA 3% and distilled water as a control on the physico-chemical properties of „Choke Anan‟ mango fruit were investigated. After dipping treatments, the fruits were stored at 2, 6 and 13 °C for 28 days and then transferred to 25 °C for 5 days shelf life. Mango stored at 2 or 6 °C, inhibited physico-chemical changes and delayed the ripening process than those stored at 13 °C. The results showed that GA 10% or CH 1% coatings significantly reduced weight loss, colour changes, soluble solid concentration, respiration rate, ethylene production and maintained higher firmness or titratable acidity than the control. GA 10% coatings formulation improved with CA 3% supplement. Another experiment was conducted to evaluate the effect of GA 10%, CA 3%, GA 10% + CA 3% or distilled water as a control on the accumulation of reactive oxygen species (ROS) and oxidative damage of mango. Mango stored at 2 °C, significantly accumulated higher ROS, malondialdehyde (MDA) content or ion leakage than those stored at 6 and 13°C. GA 10% and CA 3% treatments decreased hydrogen peroxide (H2O2) content and superoxide anion (O2 •−) production in all the three temperatures. The combined application of CA 3% and GA 10% alleviated chilling injury (CI) and oxidative damage. The third experiment was carried out to find out the effect of GA 10%, CA 3% and their combinations on enzymatic and nonenzymatic antioxidant defense system of mango stored at 6, 10 and 13 °C. The enzymatic and non-enzymatic antioxidant properties of mango were induced at 6 °C than those stored at 10 or 13 °C. Mango treated with GA 10% or GA 10% + CA 3%, enhanced catalase (CAT), ascorbate peroxidase (APX) and glutathione reductase (GR) enzyme activities. GA 10% or CA 3% treatments triggered 2, 2-diphenyl-1-picryl hydrazyl (DPPH) radical scavenging activity and preserved total phenolic content or ascorbic acid. In the fourth experiment, the ultra-structural changes in the peel of mango were investigated by transmission electron microscope (TEM). Rapid changes can be seen in the structures of cell membranes and mitochondria of mango stored at 13 °C than those stored at 6 °C. Treated mango maintained cell membranes and mitochondria structure integrity than the control. The results from all experiments suggest that mango fruit treated with GA 10% plus CA 3% can be stored at 6 °C without much deterioration.